A solid-state temporally multiplexed quantum memory array at the single-photon level - Markus Teller; Susana Plascencia; Cristina Sastre Jachimska; Samuele Grandi; Hugues de Riedmatten (npj Quantum Information)
Abstract The exploitation of multimodality in different degrees of freedom is one of the most promising ways to increase the rate of heralded entanglement between distant quantum nodes. In this paper, we realize a spatially-multiplexed solid-state quantum memory array with ten individually controllable spin-wave memory cells featuring on-demand read-out and temporal multiplexing. By combining spatial and temporal multiplexing, we store weak coherent pulses at the single-photon level in up to 250 spatio-temporal modes, with an average signal-to-noise ratio of 10(2). We perform a thorough characterization of the whole system, including its multiplexing and demultiplexing stage. We verify that the memory array exhibits low cross-talk even at the single-photon level. The measured performance indicates readiness for storing non-classical states and promises a speed-up in entanglement distribution rates.